Business mating online: The effectiveness problem of supplier selection – The case of SMEs in the United Kingdom - Zsofia Toth; Koles, B.; Marzena Nieroda (Change and transformation of markets, networks and relationships, 2016)
Recommendations are vital in building business relationships, including supplier selection. Most literature looks at referrals at an inter-personal level, even in a context where both parties are representatives of companies. There are, however, digital footprints of referrals, where the decision of providing a reference is made at an organisational level. According to the Governmental Census Statistics about 90% of volume of all electronic commerce transactions in the United States occurs in the business-to-business (B2B) arena compared to about 10% business-to-consumer (B2C) sales. The United Kingdom shows similar e-commerce patterns, yet with a B2B – B2C ratio of 3 to 1, with expected slowing growth in B2C due to maturing market dynamics and continuing growth in B2B. Despite its managerial relevance, there is a shortness of research on B2B purchase behaviour, whereas online B2C digital buying processes are researched more extensively. As pointed out by Jalkala and Salminen (2009), online referrals such as client testimonials and short case studies influence the B2B online buying process, because potential buyers can check the expertise and connections of the supplier based on whom they worked with before and whose names and logos they publish on their website. Therefore online referrals are an important B2B marketing communication tool that suppliers envisage to make themselves attractive in the eyes of potential future buyers. Tóth et al. (2015) looks at the network of corporate online referrals as a tool to map the business network and points out certain managerial practices that are based on misconceptions that can ultimately result in losing potential partners rather than extending the supplier’s network. The first misconception is that it is enough to use corporate online referrals without any strategic consideration simply because competitors do so, or going even further to not to use online referrals at all. The second misconception is that presenting oneself as bigger, more powerful, or more influential always attracts more buyers. In fact, qualitative evidence of this work suggests that in the case of SMEs, putting referrals of only large partners can discourage other SMEs to initiate the relationship with the supplier in the first place, because of being perceived as too expensive and out of their league. Instead, as buyers check online referrals when searching for new suppliers, a given supplier can increase their attractiveness via using relevant online referrals. This is especially important in certain industries where 1) the role of inter-personal relationships is less dominant; 2) the digital element of the search and buying process is prevalent; 3) market turbulence and the consequent need to build new relationships is higher and 4) the visibility of prices is limited. Despite some qualitative understanding on the role of online referrals, their impact on the intention to initiate the relationship with the supplier has not been empirically tested to date. The purpose of the current research is to address this gap, by exploring the supplier selection process of SMEs in their search for online marketing agencies. Services offered by online marketing agencies provide a good example given the growing demand for them in various sectors. Also, the search process is characteristically digital in nature, prices are usually not publicly available, and the market turbulence is relatively high due to increasing competition. The research focuses on SMEs because their buying processes are less formalised and personal perceptions play a more substantial role in their decision-making process. The current study tests the differences in the intention to initiate the relationship with the supplier in cases where there are no online referrals present in comparison to others where the company uses online referrals on their website. Behavioural differences are also tested when there are referrals exclusively from SMEs, exclusively from large corporations and mixed referrals both from SMEs and large corporations. Beyond the actual response, this setup will help investigate the extent of identity match and congruence between the SME and the potential partner. In other words, is an SME interested in partners who are similar to them in characteristics and attractiveness, or do they tend to aim higher or lower than their own league? A mixed-methods approach is applied, combining preliminary interviews and pre-tests, followed by questionnaires that incorporate an experimental research component.